Customer Preference for Consuming Organic Red Meat - Case Study of Albanian Market - Lashi, Fabjan; Kapaj, Ilir; Keco, Remzi (European Journal of Economics and Business Studies, 2017)
Albania has recognized a notable customer behavior change after 1990 CITATION Civ03 --l 1033 (Civici, 2003). These changes are still present in many aspects of customer preference, decision and continue to change dynamically. In this study we answered questions like do customers have some preference for meet originating from their localities? Is for our customers that have a relevant position for taking decisions in the family nucleus (i. e. father or mother), are most likely willing to pay price premium for organic meat? Finally, the price sensitivity also in this study persist as in important factor in deciding to purchase and pay more for organic meat. Other aspects are the need to extend the exploration in EU markets where Alania has concrete plans to become part of it, and how can undertake reforms toward becoming a full member of European Union (EU), and adopt rules and regulation to certify the organic meat. Pre-accession and later on EU accession require strict measures and a set of rules and regulations to be introduced, adopted and implemented in the agriculture sector. Food security and access in information through trusted labels are playing also a relevant role in this study.
Keywords: Organic food, meat preferences, Traceability Management Information Systems, Food Safety, Customer preference, Albania, willingness to pay.